Outcomes of mechanical support for cardiogenic shock associated with late cardiac allograft failure. Issue 12 (12th October 2020) - D'Angelo, Alex M.; Naka, Yoshifumi; Sanchez, Joseph; Kaku, Yuji; Witer, Lucas; Fried, Justin; Masoumi, Amirali; Farr, Maryjane A.; Sayer, Gabriel; Uriel, Nir; Takeda, Koji
Abstract: Background: Late graft failure (LGF) is an unresolved issue after orthotopic heart transplant (OHT). In this study, we report characteristics and outcomes of severe LGF requiring mechanical circulatory support (MCS). Methods: All patients undergoing OHT from 2000 to 2018 at our center were reviewed. Patients re‐admitted to the hospital for late graft failure (>3 months after initial discharge) and developing cardiogenic shock requiring MCS were identified. Outcomes and mortality were evaluated. Results: Twenty‐six patients were identified. Median age was 37.3 years (interquartile range: 28.2–47.6) and 69% were male. Median time from initial transplant to MCS was 2.9 years. Etiology of graft failure was rejection in 19 patients (73%), transplant coronary artery disease (tCAD) in 3 (12%), with mixed tCAD or rejection in 4 (15%).